'You Norwegians think we female Muslims are not free': enactment of gendered positional identities during transition stages. Issue 6 (18th August 2019) - Roth, Solveig; Stuedahl, Dagny
ABSTRACT: This article describes two young Norwegian ethnic-minority girls in their efforts to involve social networks and to position themselves as learners in the transition between lower and upper secondary school. The article explores how they experience future possibilities represented by education and how they use resources in negotiating their everyday lives. We use the concept of social gendered positional identities to study how educational choices are individually and collectively formed and enacted in these girls' everyday figured worlds. The study builds on ethnographic data collected by following two classmates across multiple settings over two years. We develop biographical cases to demonstrate how cultural factors relevant to learning emerged in particular contexts. The article concludes that gendered positions and choices made in educational transitions are connected and that meta-reflections on personal identity can help students to make decisions about the future.